Some epibiont suctorian ciliates from meiofaunal organisms of Maldivian archipelago with description of a new ciliate species - Ansari, Kapuli Gani Mohamed Thameemul; Guidi, Loretta; Dovgal, Igor; Balsamo, Maria; Semprucci, Federica (Zootaxa, 2017)
Five species of suctorian ciliates belonging to four different genera attached to meiofaunal organisms of Maldivian archipelago (Suvadiva Atoll) were documented. Three rare species (Acineta sp., Thecacineta urceolata Liao & Dovgal, 2015 and Limnoricus ceter Jankowski, 1981) and one common suctorian ciliate Thecacineta calix (Schröder, 1907) are re-described from nematodes (Croconema cinctum Cobb, 1920, Desmodorella tenuispiculum Allgén, 1928 and Desmodora sp.) and harpacticoid copepod basibionts. In addition, Trophogemma colantonii n. sp. colonizing the abdomen and legs of the harpacticoid copepod Stenhelia sp. is described. The new species differs from the relative species for the less flattened cell body, the absence of both lateral bundles of tentacles and separate lateral tentacles as well as for the presence of longitudinal ribs along the cuticle. The data obtained in this survey give not only new important information on the taxonomy and distribution of Suctorea, but also new insights on their relationship with meiofaunal organisms in one of the most diverse and productive marine micro-habitat of carbonate sediments.